The weight of financial instruments risk disclosure on Brazilian Banks - Costa Neto, Arlindo Menezes da (2021)
The present work has the objective of studying the value-relevance of accounting information presented by Brazilian banks. The study scope was delimited by the understanding that Banking is a segment with high concentration of financial instruments, leading, thus, to greater disclosure related risk susceptibility on such instruments. The sample here developed was chosen by the banking segment of classification on Brazil’s Stock Exchange, B3, resulting in a group of 24 publicly listed companies, whose data ranged from 2017 to 2019. The study was conducted using the disclosure index presented by Thai e Birt (2019), made with the intent to evaluate the disclosure adherence of a said company to the reporting standard, in this case, CPC 40, Financial instruments: Recognition, Evaluation and Disclosure, Instrumentos Financeiros: Evidenciação, Brazil’s interpretation of the International Financial Reporting Standards, IFRS, 7, enabling the determination of company adherence of accounting standards, on the market measurement of the value-relevance it was used the modified Ohlson (1995) model. The results show that, to the measured population and period, the Disclosure Index cannot be used as a explanatory variable for the market evaluation of the financial institutions hereby presented.